2007
DOI: 10.1101/gad.1522907
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic regulation of miRNA expression in ordered stages of cellular development

Abstract: Short RNA expression in several distinct stages of T-lymphocyte development was comprehensively profiled. The total number of microRNAs (miRNAs) expressed per cell at different stages of development varies over nearly an order of magnitude in parallel with changes in total cellular RNA content, suggesting that global miRNA levels are coregulated with the translational capacity of the cell. However, individual miRNAs were dynamically regulated during T-cell development, with at least one miRNA or miRNA family o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
387
2
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 435 publications
(429 citation statements)
references
References 50 publications
30
387
2
6
Order By: Relevance
“…As we have only measured miRNAs that are known so far, we cannot exclude that there are additional highly expressed unknown miRNAs that would raise the overall number of miRNAs per CD34+ cell. Interestingly, comparable miRNAs levels were reported by Neilson et al (2007) for cells representing different stages of T-lymphocyte development. Furthermore, it was demonstrated that global miRNA abundance is higher at high cell densities in diverse animal cell lines (Hwang et al 2009), so that the cell-cell contact in tissues could also lead to an increased overall miRNA expression.…”
Section: Discussionmentioning
confidence: 48%
“…As we have only measured miRNAs that are known so far, we cannot exclude that there are additional highly expressed unknown miRNAs that would raise the overall number of miRNAs per CD34+ cell. Interestingly, comparable miRNAs levels were reported by Neilson et al (2007) for cells representing different stages of T-lymphocyte development. Furthermore, it was demonstrated that global miRNA abundance is higher at high cell densities in diverse animal cell lines (Hwang et al 2009), so that the cell-cell contact in tissues could also lead to an increased overall miRNA expression.…”
Section: Discussionmentioning
confidence: 48%
“…It has been shown that miRNAs expressed at low levels (< 100 copies per cell) did not significantly repress target-containing transcripts [42], since target encounter occurs by mass action and modestly expressed miRNAs have a low probability to meet target-containing transcripts. Previous measurements of miRNAs in liver samples revealed that let-7a, miR-16, miR-20, miR-21, and miR-22 were present at 700, 3 890, 130, 4 450, and 310 copies per cell, respectively [43], while miR-181a was expressed at 810 copies per cell in DP thymocytes [44] and miR-223 and miR-451 were 828 and 1 972 copies per cell in CD34(+)/CD133(−) cells [45]. It has been widely demonstrated that miRNAs expressed at these concentrations are biologically active [46][47][48][49].…”
Section: Ago2-associated Mature Mir168a In Mvs Is the Functional Formmentioning
confidence: 99%
“…Thus, sponges show direct effects on natural and endogenous targets, and can be used to validate target predictions. To test some predicted targets that had not yet been experimentally validated, we used a luciferase reporter regulated by a large fragment of the CD69 3′ UTR 17 or by the E2F5 UTR. As predicted by the TargetScan 4.0 and miRanda algorithms, respectively, these UTRs are each regulated by a single miR-20 site 18,19 .…”
Section: Validation Of Predicted Microrna Targetsmentioning
confidence: 99%